Integration, resources reallocation and productivity: The cases of Brazil and Chile - Juan Blyde; Gonzalo Iberti; Mauricio Mesquita Moreira (Inter-American Development Bank (IDB), 2009)
Most microeconometric studies available for LAC have focused on measuring the direct impact of trade on plant productivity leaving aside other effects that arise through the market selection process. Additionally, most studies have focused on tariff barriers as the only obstacle to international trade and integration. In this paper we use data from Brazil and Chile to analyze how trade affects aggregate productivity through the process of resource reallocation and to explore not only the role of tariffs but also the role of transport costs. We find that trade costs affect the reallocative process by protecting inefficient producers, lowering their likelihood to exit, and also by limiting the expansion of efficient plants, lowering their likelihood to export. We also find that the reallocative impacts of trade come not only from tariff barriers but also from transport costs.
hdl:11319/2548
Keywords: F13; F14; 330; Tariff barriers; transport costs; productivity; resource reallocation